Authentication Methods in Modern Web Services - Marcin SOBOTA; Bartosz Stolarek (Communications of International Proceedings, 2022)
This article presents comparative analysis of selected authentication methods used in modern Web services. Conducted study was based on analyzing level of implementation complexity in JavaScript programming language and Node.js environment, on analyzing security level that certain authentication methods could provide, and popularity of authentication methods based on data coming from Stack Overflow and Google Search websites. Conducted study lead to defining complexity, security, and popularity levels of selected authentication methods, which are key factors in the process of choosing authentication methods for modern Web architectures.
Keywords: authentication methods; Web services; network communication; data storage; JavaScript; Node.js.